Detecting leakage current by infrared thermography method - M Riduan B. M Shariff; M.F. L. Abdullah; M Yusop B. A Latiff; Ahmad B. Mohamad; Iszaizul B. Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
An alternating current leakage can happen in electrical installation such as switchgear panel. If it’s not being detected earlier and address properly, it might lead to unintended incident or accident such as fire, electric shock, and power supply trip. Occasionally, if it appears, tracing its root cause can be difficult. The conventional method is by isolating one by one of the electrical loads with aids of multimeter and clamp meter.  Unfortunately, this conventional method could be a tedious job for installations involved in numbers of electrical panels. Therefore, an alternative method is deeming necessary. This paper describes research works on Infrared Thermography (IRT) as a new method in detecting leakage current as aids in resolving related electrical problems. The scope of study mingling around to determine IRT’s suitable parameters that represent the identification of leakage current, derive new mathematical equation correlating leakage current to IRT and conduct experiment accordingly. Two new equations derived which are leakage current relationship to thermogram and infrared net radiation power. The results of experiment adherence to the hypothesis drawn. Consequently, helps to realize predictive maintenance concept by detecting the root cause of leakage current ahead its triggering points of unintended incident and accident.